(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Internet of things is latest rapidly growing technology. IOT is the system of interrelated computing devices and objects integrated with electrical devices, applications, sensors, and internet, which allows objects to bring and interchange data. This latest machinery has provided a chance to build advanced industry and its new applications. In this paper, a system is developed that automatically monitor the industry system and generate alert and alarms or take better decisions using concept of IoT. Iot has given us promising way to build powerful industrial systems and program by using smart devices, android applications and sensors.